Seasonal ARIMA Forecasting of MSME Sales: A Case Study on KleponHolic - Nizam, Muh. Syariel; Razak, Muhammad Rais Rahmat; Syafaruddin, Andi Riska Andreani; Ramlan, Pratiwi (Institut Agama Islam Negeri Kendari, 2025)
This research focuses on analyzing sales forecasting using the Seasonal ARIMA method on KleponHolic business, a culinary MSME in Sidenreng Rappang Regency. This research aims to identify seasonal patterns in KleponHolic’s sales data, measure the accuracy of the Seasonal ARIMA method in sales forecasting, and provide strategic recommendations for the business in optimizing stock management and data-based marketing. This research uses a descriptive quantitative approach with the Univariate Time Series Analysis method, in which the data used is historical sales data of KleponHolic from 2021 to 2024. The data collection techniques used in this research consist of observation to directly observe KleponHolic’s business operations, documentation study to obtain sales data, and informant information to validate the forecasting results. Data analysis is carried out using the Seasonal ARIMA method, which consists of seven stages, including data exploration, stationarity test, model identification, parameter estimation, model diagnostics, forecasting, and interpretation of results. Keywords: Forecasting; Seasonal ARIMA; sales forecasting. JEL classification: E17, C22, M31